Relevansi Pemikiran Politik R.A. Kartini dalam Politik Perempuan Indonesia: Perspektif Politik Gender dan Relasi Kuasa - Maya Dina Rahma Maghfiroh; Agustinus Sugeng Priyanto (Pusat Riset dan Inovasi Nasional, 2026)
Gender inequality in Indonesian politics forms part of broader structural and cultural dynamics that shape women’s positions in the public sphere. In historical studies, the thought of R.A. Kartini is often interpreted primarily as a symbol of educational and moral emancipation, while the political dimension of her ideas receives limited attention. This study aims to examine Kartini’s political thought as reflected in her letters, positioning her as a political subject who articulated critiques of social structures, customary norms, and patriarchal power relations through non-formal means. This research adopts a qualitative approach with a library-based research design. The data are derived from an analysis of Kartini’s letters compiled in Door Duisternis tot Licht and supported by relevant academic literature. A descriptive-analytical method with a thematic approach is employed to explore political ideas and discourses embedded in the texts. Kartini’s thought in this study is understood as a form of political awareness that extends beyond individual emancipation and relates to broader issues of women’s political participation. This research contributes to the study of women’s politics by offering a historical perspective that places women as political subjects.